Evaluación de la viabilidad económica de un sistema de acuaponía en el contexto regional colombiano, a partir de sus costos generalizados (2023)
The study investigates the cost-benefit ratio of a sustainable aquaponics system that combines aquaculture and hydroponics. A financial analysis methodology is used that considers costs of materials, labor and operating expenses, as well as possible income from the sale of products. The objective is to provide information for the implementation of small or medium scale aquaponics systems, demonstrating their viability as a profitable and sustainable option. This approach seeks to promote aquaponics as a beneficial technique to improve quality of life and the environment.